A Case of COVID-19 Complicated by Venous Thromboembolism Despite Being on Prophylactic Anticoagulation - Rout, Amit (J Med Cases, 2020)
The coronavirus disease 2019 (COVID-19) presents with variable clinical syndromes, from asymptomatic disease to acute respiratory failure. Complications such as acute respiratory distress syndrome (ARDS), secondary infection, acute cardiac injury, liver failure, renal failure, coagulable disorders and in many cases, death have been recognized. Venous thromboembolism (VTE) was found to be present in up to one-third of critically ill COVID-19 patients. Our case demonstrated a patient with COVID-19 who developed a massive pulmonary embolism leading to cardiac arrest, despite having an initial normal D-dimer level, normal chest imaging, and while maintained on appropriate VTE prophylaxis during hospitalization.